Particulate matter exposure in construction sites is associated with health effects in workers - Sekhavati, Eghbal; Yengejeh, Reza Jalilzadeh (Frontiers in Public Health, 2023)
Background Exposure to suspended particulate matters (PMs) at high concentrations, mainly observed in the construction workplace, is found to be a risk factor for major health outcomes. The present study was conducted to investigate the degree of exposure to suspended PMs in different stages of construction of the buildings and the health risk associated with the exposure in Lar, Fars, Iran. Methods In this cross-sectional study, two construction sites were selected in Lar. Cancer and non-cancer health risks of exposure to PM2.5 and PM10 were assessed using the US Environmental Protection Agency method in three-dimensions: inhalation, digestion, and dermal absorption. The hazard quotient (HQ) and total cancer risk (TCR) were considered as parameters for risk analysis. Results The highest level of non-cancer risk for workers in the concentrations of PM2.5 and PM10 particles in the drilling process were determined to be 2.97 × 10−1 and 8.52 × 10−2, respectively. In the cancer risk analysis, PM10 concentrations were estimated to be at the highest level (1.7 × 10−7) in the drilling process and the lowest level (4.29 × 10−8) in the facilities process. For suspended PM2.5, it was an unacceptable risk level in all processes, except for the implementation of facilities. Conclusion These results show that the construction industry, especially in developing countries such as Iran, needs better management to maintain the health of construction workers.